In vitro biomechanical and hydrodynamic characterisation of decellularised human pulmonary and aortic roots. (March 2018) - Desai, A.; Vafaee, T.; Rooney, P.; Kearney, JN.; Berry, HE.; Ingham, E.; Fisher, J.; Jennings, LM.
Abstract: Background and purpose of the study: The use of decellularised biological heart valves in the replacement of damaged heart valves offers a promising solution to reduce the degradation issues associated with existing cryopreserved allografts. The purpose of this study was to assess the effect of low concentration sodium dodecyl sulphate decellularisation on the in vitro biomechanical and hydrodynamic properties of cryopreserved human aortic and pulmonary roots. Method: The biomechanical and hydrodynamic properties of cryopreserved decellularised human aortic and pulmonary roots were fully characterised and compared to cellular human aortic and pulmonary roots in an unpaired study. Following review of these results, a further study was performed to investigate the influence of a specific processing step during the decellularisation protocol ('scraping') in a paired comparison, and to improve the method of the closed valve competency test by incorporating a more physiological boundary condition. Results: The majority of the biomechanical and hydrodynamic characteristics of the decellularised aortic and pulmonary roots were similar compared to their cellular counterparts. However, several differences were noted, particularly in the functional biomechanical parameters of the pulmonary roots. However, in the subsequent paired comparison of pulmonary roots with and without decellularisation, and when a more appropriate physiological test model was used, the functional biomechanical parameters for the decellularised pulmonary roots were similar to the cellular roots. Conclusion: Overall, the results demonstrated that the decellularised roots would be a potential choice for clinical application in heart valve replacement.